Implications of pH and Ionic Environment in Chronic Diabetic Wounds: An Overlooked Perspective - Guo J; Cao Y; Wu QY; Zhou YM; Cao YH; Cen LS (Dove Medical Press, 2024)
Jing Guo,1 Yi Cao,1 Qing-Yuan Wu,2 Yi-Mai Zhou,3 Yuan-Hao Cao,3 Lu-Sha Cen4 1Department of Dermatology. The First Affiliated Hospital of Zhejiang Chinese Medical University (Zhejiang Provincial Hospital of Chinese Medicine), Hangzhou, ZheJiang Province, People's Republic of China; 2Department of Respiratory & Critical Care Medicine.The First Affiliated Hospital of Zhejiang Chinese Medical University (Zhejiang Provincial Hospital of Chinese Medicine), Hangzhou, ZheJiang Province, People's Republic of China; 3The First Clinical Medical College, Zhejiang Chinese Medicine University, Hangzhou, Zhejiang Province, People's Republic of China; 4Department of Ophthalmology. The First Affiliated Hospital of Zhejiang Chinese Medical University (Zhejiang Provincial Hospital of Chinese Medicine), Hangzhou, ZheJiang Province, People's Republic of ChinaCorrespondence: Lu-Sha Cen, Email 201811010712026@zcmu.edu.cnAbstract: The high incidence of disability and fatality rates associated with chronic diabetic wounds are difficult problems in the medical field. The steady-state and regular changes of the microenvironment in and around the wound provide good conditions for wound healing and achieve a dynamic and complex process of wound healing.The pH value and ionic environment composed of a variety of ions in wound are important factors affecting the wound microenvironment, and there are direct or indirect connections between them. Abnormalities in pH, ion concentrations, and channels in skin tissue may be one of the reasons for the high incidence and difficulty in chronic diabetic wounds healing. Currently, different wound-dressing applications have been developed based on the efficacy of ions. Here, the effect of pH in wounds, concentrations of calcium (Ca2+), sodium (Na+), potassium (K+) and the metal ions silver (Ag+), copper (Cu2+), iron (Fe2+/Fe3+), zinc (Zn2+), and magnesium (Mg2+) in skin tissue, their roles in wound healing, and the application of related dressings are reviewed. This manuscript provides new ideas and approaches for future clinical and basic research examining the treatment of chronic diabetic wounds by adjusting ion concentrations and channels. Keywords: Chronic diabetic wounds, pH, Ions, Ionic environment, Wound healing, Review